Can measuring urinary biomarkers improve the management of lupus nephritis? - Rahman, Anisur (BioMed Central, 2012)
Although renal biopsy is the most accurate way of assessing renal inflammation in patients with lupus nephritis (LN), the technique is invasive and cannot be performed frequently. Currently used blood and urine biomarkers have limited utility in monitoring the activity of nephritis. In a previous issue of Arthritis Research and Therapy, Singh and colleagues showed that measuring urinary levels of vascular cell adhesion molecule 1 could be useful in both diagnosing and monitoring LN. These levels are higher in patients with lupus than controls, are higher in lupus patients who have active renal disease compared with those who do not, and correlate significantly with the histological activity index in renal biopsies of patients with LN.